Genre Analysis of Undergraduate Dissertation Abstracts in Two Disciplines - Emmanuel Mensah Bonsu (English Department of Faculty of Tarbiyah and Teacher Training, 2021)
This research departed from the result of training on the development of online learning design for secondary school teachers before the pandemic. On that training, WhatsApp is the best choice to be implemented by the teachers. In this research, WhatsApp-based learning design is chosen to facilitate English teachers during learning from home. As a result, the impact for students is that their learning outcomes were positively correlated to their perception, knowledge, motivation, and attitudes during learning from home using WhatsApp. Then, the implication of this research is that English teachers have competitiveness and also competence in the utilization of digital technology, especially in developing English learning designs while they taught from home.